2017
DOI: 10.7150/ijms.18054
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Metoprolol Succinate in Patients with Stable Angina and Elevated Heart Rate Receiving Low-Dose β-Blocker Therapy

Abstract: Aims: β-blockers are underused in Chinese patients with coronary heart disease. The prescribed dose is often low. The aim of this study was to investigate the effect of metoprolol succinate doses of 95 mg and 190 mg on heart rate (HR) control, as well as drug tolerance, in Chinese patients with stable angina, low-dose β-blocker use and unsatisfactory HR control.Methods: This was a multicenter, randomized, open-label, parallel-group trial in 15 clinical sites. Patients with stable angina, taking low-dose β-bloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Further, if the drug is well-tolerated it can be titrated to 200 mg/day 4. Recently, an investigation indicated that 190 mg metoprolol succinate was well-tolerated for Chinese patients 11…”
Section: Introductionmentioning
confidence: 99%
“…Further, if the drug is well-tolerated it can be titrated to 200 mg/day 4. Recently, an investigation indicated that 190 mg metoprolol succinate was well-tolerated for Chinese patients 11…”
Section: Introductionmentioning
confidence: 99%